2016
DOI: 10.1111/ijfs.13014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mentha spicata L. and Mentha aquatica L. essential oils on the microbiological properties of fermented dairy product, kashk

Abstract: The antibacterial activity of Mentha spicata and Mentha aquatica essential oils (EO) was tested against Staphylococcus aureus, Lactobacillus reuteri, Bifidobacterium animalis and Clostridium perfringens using agar well and disc diffusion techniques. Results showed that M. spicata EO had the highest inhibition activity against the studied microorganisms. Then, the antibacterial activity of both EO at 1500 and 2500 ppm was examined in industrial liquid kashk during the storage at 4°C for 20 days. Both EO reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
4
18
2
1
Order By: Relevance
“…M. arvensis was effective at the same concentration against both biofilm producing staphylococcal strains (CCM 3953 and CCM 4223) (Table 6). The antibacterial activity of M. spicata was confirmed also in the study by G o l e s t a n et al [5]. They observed that M. spicata EO had the highest inhibition activity against S. aureus and Clostridium perfringens.…”
Section: Determination Of Micsupporting
confidence: 63%
“…M. arvensis was effective at the same concentration against both biofilm producing staphylococcal strains (CCM 3953 and CCM 4223) (Table 6). The antibacterial activity of M. spicata was confirmed also in the study by G o l e s t a n et al [5]. They observed that M. spicata EO had the highest inhibition activity against S. aureus and Clostridium perfringens.…”
Section: Determination Of Micsupporting
confidence: 63%
“…Although various studies have been carried out on the efficacy of plant EOs in the different dairy products as a food system such as cheese (Gandomi et al, ; Smith‐Palmer, Stewart, & Fyfe, ), milk (Cava, Nowak, Taboada, & Marin‐Iniesta, ), yogurt drink and yogurt (Athary, Saeidiasl, Elhamirad, & Armin, ; Evrendilek & Balasubramaniam, ; Gurdip, Singh, & Pratibha, ), and kashk. (Golestan, Seyedyousefi, Kaboosi, & Safari, ), no studies have been found which investigate the antifungal activity of plant EOs in Doogh.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to apply EOs in food model systems, potential interactions between EOs and food components and also the impact of EOs on organoleptic properties and consumer acceptability in foods should be considered (Gutierrez, Barry-Ryan, & Bourke, 2008 Gurdip, Singh, & Pratibha, 2011), and kashk. (Golestan, Seyedyousefi, Kaboosi, & Safari, 2016), no studies have been found which investigate the antifungal activity of plant EOs in Doogh.…”
Section: Introductionmentioning
confidence: 99%
“…The hydro-distillation of mint aerial parts provides EO, the chemical composition of which varies with species. M. arvensis EO has a high proportion of isomenthone and menthol, M. spicata has an EO rich in limonene, carvone, and caryophyllene, [8] and M. piperita produces an EO rich in menthol and menthyl acetate. [9] The study of the antimicrobial activity of mint EO has shown contrasting results, although this difference is mainly due to the differences in chemical composition and, to a lesser extent, the experimental protocol utilized.…”
Section: Introductionmentioning
confidence: 99%